Organizational Flexibility and Financial Performance: A Case Study of Social Security Branches in Tehran - Mona Dastam (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Organizational flexibility has become an undeniable necessity in today's uncertain and dynamic environment. It allows the organization to respond appropriately to environmental changes, which can even affect its financial performance. The present study investigates the relationship between organizational flexibility and financial performance. Methodology: The present study is one of those applied research studies whose information was collected using a survey method. It is of correlation type because it examines the relationship between organizational flexibility and financial performance. Findings: The results show that organizational flexibility has a positive and significant relationship with financial performance. In other words, planned and adaptive flexibility have an essential relationship with financial performance, and the path coefficient of adaptive flexibility is higher than that of planned flexibility. Originality/Value: The originality and value of the text lie in its contribution to understanding the critical link between organizational flexibility and financial performance, offering practical insights for managerial decision-making in navigating today's dynamic business environment.